PENGARUH DEBT TO EQUITY RATIO, EARNING PER SHARE, DAN MARKET VALUE ADDED TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2015-2017 - Risky Okta Dwi Putra; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine Effect of Debt to Equality Ratio (DER), Earning per Share (EPS), Market Value Added and to the Company's Stock Prices Registered in the Jakarta Islamic Index partially or simultaneously. The population in this study are companies listed in the Jakarta Islamic Index (JII). The sample used in this study were 14 companies registered in the Jakarta Islamic Index that met the criteria of purposive sampling. The research observation period starts from 2015 to 2017.Keywords: DER, EPS, Market Value, JII